2008
DOI: 10.1364/oe.16.003753
|View full text |Cite
|
Sign up to set email alerts
|

Using a pair of rectangular coils in the MOT for the production of cold atom clouds with large optical density

Abstract: We demonstrate a simple method to increase the optical density (OD) of cold atom clouds produced by a magneto-optical trap (MOT). A pair of rectangular anti-Helmholtz coils is used in the MOT to generate the magnetic field that produces the cigar-shaped atom cloud. With 7.2x10(8) (87)Rb atoms in the cigar-type MOT, we achieve an OD of 32 as determined by the slow light measurement and this OD is large enough such that the atom cloud can almost contain the entire Gaussian light pulse. Compared to the convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…We also demonstrated that the classical fidelity of the recall pulse is better than 90% as measured by a beat-note interferometer [27]. Our results suggest that EIT-based quantum memory can be used for practical quantum information applications.The experiment was carried out in a cigar-shaped cloud of cold 87 Rb atoms produced by a magneto-optical trap (MOT) [28]. Typically, we trapped 1.0 × 10 9 atoms with…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also demonstrated that the classical fidelity of the recall pulse is better than 90% as measured by a beat-note interferometer [27]. Our results suggest that EIT-based quantum memory can be used for practical quantum information applications.The experiment was carried out in a cigar-shaped cloud of cold 87 Rb atoms produced by a magneto-optical trap (MOT) [28]. Typically, we trapped 1.0 × 10 9 atoms with…”
mentioning
confidence: 99%
“…The experiment was carried out in a cigar-shaped cloud of cold 87 Rb atoms produced by a magneto-optical trap (MOT) [28]. Typically, we trapped 1.0 × 10 9 atoms with |m=1¡ |m=2…”
mentioning
confidence: 99%
“…Since the first demonstrations in 2001 [13,14], EIT storage has been studied in both hot atomic vapor cells [15][16][17] and cold atoms [18][19][20][21]. However, the reported experimental demonstration always has a very low storage efficiency that prevents it from practical applications.…”
mentioning
confidence: 99%
“…The atom cloud had a cigarlike shape with a size of about 10×2.5×2.5 mm 3 . Details of our MOT setup and the production of the cigar-shaped atom cloud have been discussed elsewhere [10]. Figure 2 shows the experimental setup and the transition diagrams.…”
mentioning
confidence: 99%